PREVALENCE OF DEPRESSIVE SYMPTOMS AND RISK FACTORS IN MEDICAL STUDENTS (CIPEEX, 2022)
DEPRESSION IS THE MOST RECURRENT MENTAL HEALTH DISORDER OF THE 21ST CENTURY. THEY CONTRIBUTE TO THIS, THE CURRENT EPHEMERAL, EXHAUSTING AND MATERIALISTIC REALITY. IN THIS CONTEXT, MEDICAL STUDENTS ARE POTENTIAL VICTIMS BECAUSE THEY LIVE AN EXTREMELY ARDUOUS ROUTINE, CHARACTERIZED BY THE EXCESS OF CONTENTS COVERED DURING THE COURSE, A STRENUOUS WORKLOAD BEYOND LEISURE DEPRIVATION. SUCH CONDITIONS POTENTIATE THE RECURRENCE OF DEPRESSION IN THIS GROUP OF ACADEMICS. THE FOLLOWING PAPER IS AN EXPANDED SUMMARY, BASED ON 5 STUDIES FROM THE SCIELO AND PUBMED DATABASE, IN ORDER TO IDENTIFY THE MAIN FACTORS ASSOCIATED WITH THE ONSET OF DEPRESSIVE SYMPTOMS AND THE PREVALENCE OF DEPRESSIVE SYMPTOMS AMONG MEDICAL STUDENTS.
Keywords: Depressive symptoms. Medical students. Prevalence of depression.